Symbiotic Society with Avatars (SSA): Beyond Space and Time - Hedayati, Hooman; Seo, S.; Kanda, T.; Rea, Daniel J.; Andrist, Sean; Nakano, Y.; Ishiguro, H. (Companion of the 2023 ACM/IEEE International Conference on Human-Robot Interaction, 2023)
Avatar robots can help people extend their physical, cognitive, and perceptual capabilities, allowing people to exceed time and space constraints. In that sense, avatar robots can greatly influence people's lives. However, we have many challenges to be addressed in various scenarios such as avatar-human interaction, operator-avatar interaction, avatar-avatar interaction, ethical and legal issues, technical challenges, and so on. It is indispensable to discuss what the necessary research and technologies are to realize avatars that are well accepted in society while envisioning a future symbiotic society in which people communicate with other people and their avatars. In our previous workshop "Symbiotic Society with Avatars: Social Acceptance, Ethics, and Technologies (SSA)" we focused on the ethical aspect of avatars. In this workshop, our aim is to provide an opportunity for researchers from different backgrounds including social robotics, teleoperation, and mixed reality to come together and discuss the advances and values in a symbiotic society with avatars.